The role of party autonomy under the regulations on matrimonial property regimes and property consequences of registered partnerships. Some remarks on the coordination between the legal regime established by the new regulations and other relevant instrume: Some remarks on the coordination between the legal regime established by the new regulations and other relevant instruments of European Private International Law - Grieco, Cristina (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The new Regulations (No. 2016/1103 and No. 2016/1104) recently adopted through an enhanced cooperation by the European Legislator aim to deal with all the private international law aspects of matrimonial property regimes and property consequences of registered partnerships, both as concerns the daily management of matrimonial property (or partner’s property) and its liquidation, in particular as a result of the couple’s separation or the death of one of the spouses (or partners). This paper aims to address the prominent role of party autonomy in the two Regulations and to focus on the coordination between the legal system embodied in the new two Regulations, and other relevant instruments of European private international law in force, such as the Succession Regulation and the Bruxelles II- bis Regulation.